Prophylactic anti-coagulation after severe burn injury in critical care settings - Blake, Megan; Roadley-Battin, Ruth; Torlinski, Tomasz (Acta medica Lituanica, 2019)
Background. Severely burnt patients are at an increased risk of thromboembolic complications, hence sufficient prophylactic anticoagulation is of paramount importance. Local guidelines at the Burns Centre in the Queen Elizabeth Hospital, Birmingham therefore advise increasing the standard dose of low molecular weight heparin in these patients. An audit was carried out to assess the current practice in burns patients to ensure adequate anticoagulation and adherence to guidelines. Materials and methods. Retrospective data was collected on all burns patients in the Burns Centre over a two-year period. The main objectives were to assess: • anticoagulation regimes prescribed to severe burns patients • monitoring of Anti-Factor Xa levels • adjustment of dosing based on the results The locally produced trust guidelines were used as the comparator. Results. All burns patients were prescribed anticoagulation, but often the dose was not increased as suggested in the guidelines. Although most of the severely burnt patients were prescribed adjusted higher doses of anti-coagulation, only 60% of these patients were monitored with Anti-Factor Xa assays. Of these assays, 66% showed sub-prophylactic levels. The majority of results led to the adjustment of the dose of anticoagulant. However, often dose changes were made late. Discussion and conclusions. The audit confirmed the need for increased doses of prophylactic anticoagulation in severe burns. The better adherence to the guidelines can be achieved by additional training and implementation of decision support via electronic prescribing system.
Keywords: anticoagulation; thromboprophylaxis; burns; intensive care; heparin; Anti-Factor Xa; thermal trauma